Delivery of Molecules Using Nanoscale Systems for Cancer Treatment and/or Diagnosis (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This book focuses on how nanoscale systems can be used to deliver molecules to help with cancer management. It provides a broad overview of some of the key strategies for nanocarrier design. These strategies are brought together by the wide compositional variety of these systems and the diversity of molecules that may be carried. Additionally, functionalization strategies, codelivery, and combination with other treatment modalities highlight a very active research field.